Rekonstruksi Toleransi Beragama Umat Hindu dan Islam di Desa Tembok Kecamatan Tejakula Kabupaten Buleleng - Heriyanti, Komang; Yudha Triguna, Ida Bagus Gde; Wirawan, I Gusti Bagus (Jurnal Penelitian Agama Hindu, 2025)
Tembok Village as part of Buleleng Regency is inhabited by people of different religions, namely Hindus and Muslims. The relationship between the two communities from the beginning has been based on the values ​​of tolerance. Although in some conditions there was a decline in tolerance, this was strengthened by the reconstruction of religious tolerance such as silaturahmi during religious holidays. The purpose of this study is to provide an overview of the importance of tolerance for a pluralistic society like in Indonesia. Activities that have a nuance of tolerance in Tembok Village can be considered in strengthening the bonds of tolerance in certain areas. The method used in this study is a qualitative method, by exploring the phenomena that occur in the field related to the social life of Hindus and Muslims in Tembok Village. The results of the field research explain that the process of reconstruction of religious tolerance is carried out during religious holidays such as Galungan, Eid al-Fitr, and Eid al-Adha. Furthermore, regarding the implications of the reconstruction of religious tolerance, it explains that it has implications for social, cultural, and religious life. It can be concluded that the reconstruction of religious tolerance in Tembok Village is able to bring positive implications for society. Where society better understands the importance of tolerance in social life.